Randomised trial comparing weight loss through lifestyle and GLP-1 receptor agonist therapy in people with MASLD - Ahmad Moolla; Toryn Poolman; Nantia Othonos; Jiawen Dong; Kieran Smith; Thomas Cornfield; Sarah White; David W. Ray; Sofia Mouchti; Ferenc E. Mózes; Helena Thomaides-Brears; Stefan Neubauer; et al. (JHEP Reports)
Background & Aims: Glucagon-like peptide 1 receptor agonist (GLP-1RA) therapies deliver histological benefit in people with metabolic dysfunction-associated steatotic liver disease (MASLD). Multiple mechanisms may be important including weight loss, improved glycaemic control and putative direct tissue-specific actions. Following cessation of GLP1-RA therapy, weight regain is common. To dissect the mechanisms underpinning their benefits, we conducted a prospective, randomised, experimental medicine study in people with MASLD, comparing GLP-1RA treatment (liraglutide) to matched lifestyle-induced weight loss and assessed the impact of treatment withdrawal. Methods: Twenty-nine participants with MASLD, without type 2 diabetes underwent metabolic phenotyping including measurement de novo lipogenesis (DNL), liver magnetic resonance imaging, body composition, adipose tissue RNA sequencing, circulating proteome, and stool microbiome analysis. Participants were randomised to lifestyle (∼500 kcal energy deficit) or GLP1-RA treatment for 12 weeks, after which investigations were repeated, and treatment stopped; investigations were also repeated 12 weeks after treatment withdrawal. Results: Matched weight loss was achieved in both arms. Body composition changes, reductions in alanine aminotransferase, liver steatosis, and disease activity were similar following both treatments. GLP-1RA treatment, but not lifestyle, improved glucose handling, fasting lipids, and significantly deceased DNL. The subcutaneous adipose transcriptome, circulating proteome profile and stool microbiome were not different between groups after treatment. However, 12 weeks after GLP1-RA (but not lifestyle) withdrawal, circulating MMP-10, IL10RB, FGF-23, and Flt3L were elevated, alongside dysregulated adipose gene expression. Conclusions: Although matched weight loss through lifestyle or GLP-1RA have comparable effects on hepatic steatosis, GLP-1RA treatment had additional metabolic benefits on glucose homeostasis, lipid profiles, and DNL. However, GLP-1RA withdrawal may adversely impact the circulating proteome, adipose tissue gene expression, and the stool microbiome, predisposing to weight regain. Impact and implications: Weight loss, through either lifestyle intervention or pharmacotherapy with GLP-1RA has an equally beneficial impact on the liver, and both strategies should be considered in the management of people with MASLD. GLP-1RA therapy may have additional benefits to improve glucose homeostasis even in the absence of pre-existing type 2 diabetes. Further research is needed to explore the differential impact of treatment withdrawal and the resultant metabolic consequences. Clinical Trials Registration: This study is registered at EudraCT (2016-002045-36).